2010
DOI: 10.1002/cphc.201000212
|View full text |Cite
|
Sign up to set email alerts
|

Study of Carbon Monoxide Oxidation on Mesoporous Platinum

Abstract: H(1) mesoporous platinum surfaces formed by electrodeposition from lyotropic liquid crystalline templates have high electroactive surface areas (up to 60 m(2) g(-1)) provided by the concave surface within their narrow (≈2 nm diameter) pores. In this respect, they are fundamentally different from the flat surfaces of ordinary Pt electrodes or the convex surfaces of high-surface-area Pt nanoparticles. Cyclic voltammetry of H(1) mesoporous Pt films in acid solution is identical to that for polycrystalline Pt, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
2
5
0
Order By: Relevance
“…The nanoparticles with the lowest Pt coverage exhibit the lowest activity, with a broad wave followed by another wave at more positive potentials. The nanoparticles prepared by the selective blocking method produce CVs with a sharp peak centered at more negative potentials, reminiscent of similar measurements on polycrystalline Pt, 35 and with higher overall charge than for CVs of the other samples. The sharpness of the peak, along with the CVs of the clean NR surfaces, indicates that the selective blocking method yields NRs with more extended regions of Pt surface.…”
Section: Resultssupporting
confidence: 62%
“…The nanoparticles with the lowest Pt coverage exhibit the lowest activity, with a broad wave followed by another wave at more positive potentials. The nanoparticles prepared by the selective blocking method produce CVs with a sharp peak centered at more negative potentials, reminiscent of similar measurements on polycrystalline Pt, 35 and with higher overall charge than for CVs of the other samples. The sharpness of the peak, along with the CVs of the clean NR surfaces, indicates that the selective blocking method yields NRs with more extended regions of Pt surface.…”
Section: Resultssupporting
confidence: 62%
“…Furthermore, the CO stripping is a powerful technique for the study of the surface morphology and structure. In addition, CO stripping is a convenient method to obtain an accurate estimation of the electroactive surface area [26,41].…”
Section: Co Strippingmentioning
confidence: 99%
“…the porous radio can be adjusted by the choice of the appropriated surfactant, and additional porosity can be introduced by the selection of the applied potential). The resulting catalysts possess an extremely concave mesoporous surface, and this characteristic may, by itself, affect the CO electrooxidation reaction [26].…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with this idea, a recent paper by Esterle et al has suggested that the concave curvature of nanoporous platinum electrodes is responsible for the low-potential CO stripping peak on such electrodes. 62 As mentioned, a much-debated issue in CO oxidative stripping has been the role of surface diffusion of CO from the less active terrace sites to the more active step sites. Clearly, the issue of surface diffusion will apply to class IV reactions in general.…”
Section: Structure Sensitivity: Experimental Observationsmentioning
confidence: 99%